Obesity and Hypertension in Students of Jahangirnagar University: Alarming Issues - Sudip Paul; Md. Solayman; Puja Biswas; Moumoni Saha; Md. Sabir Hossain (International Journal of Public Health Science (IJPHS), 2015)
The prevalence of obesity and hypertension (HTN) in university students of Bangladesh has not reported yet. Considering the proper health maintenance of this population in mind, the study was aimed to determine the prevalence of obesity and HTN as well as relationship among them in the students of a residential university of Bangladesh, Jahangirnagar University. This descriptive cross sectional study included 500 randomly selected students (250 males and 250 females). Participants completed a questionnaire on physical activity, sedentary behaviour, dietary factors, smoking and family history of obesity, HTN, and coronary artery disease. Blood pressure and anthropometric parameters such as height, weight, waist and hip circumferences were measured following standard procedure. The Statistical analyses were performed using the software SPSS.The prevalence of overweight was 25% (31.1% males, 15.6% females) and obesity 7.2% (9.4% males, 4% females). Pre-HTN was found at 27.1% (38% males, 11.2% females) and HTN at 2.2% (3.3% males, 0.4% females). A high rate of smoking, sedentary behavior, physical inactivity, excessive consumption of unhealthy food, and caffeine-rich drinks was also observed. Significant correlation was found between parameters of obesity and HTN. High prevalence of pre-HTN in males and central obesity in females were found which is immediately needed to control for better health maintenance of this population.